2021
DOI: 10.1080/2331186x.2021.1888672
|View full text |Cite
|
Sign up to set email alerts
|

Inside the intention to join extracurricular activities: Integrating the theory of planned behavior and signaling theory

Abstract: Although researchers have previously discussed the consequences of extracurricular activity (ECA) participation, the question of which factors affect the intention to participate in ECAs has been less addressed. By incorporating the theory of planned behavior (TPB) and signaling theory, this study investigates the role of the components of the TPB and signal quality in the intention to join ECAs. In addition, the contingent effects of students' demographic profiles, such as their gender, their year in school, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 55 publications
0
8
0
1
Order By: Relevance
“…However, while ECAs influence student motivation, what motivates students to participate in ECAs remains unclear. Conversely, Dang and Nguyen Viet [16] looked at the antecedents by combining the theories of planned behavior [1] and signaling [66]. This study used demographic, information quality, capability, and motivation (i.e., attitude and subjective norm) factors to determine what influences students to participate in ECAs.…”
Section: Research Model and Hypotheses Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…However, while ECAs influence student motivation, what motivates students to participate in ECAs remains unclear. Conversely, Dang and Nguyen Viet [16] looked at the antecedents by combining the theories of planned behavior [1] and signaling [66]. This study used demographic, information quality, capability, and motivation (i.e., attitude and subjective norm) factors to determine what influences students to participate in ECAs.…”
Section: Research Model and Hypotheses Developmentmentioning
confidence: 99%
“…Prior works have shown that the demographic profile influences students' intention to participate in ECAs [16,57]. These factors may also affect the interrelationships between the core variables in the hackathon context.…”
Section: Analysis Of Demographic Profiles As Control Variablesmentioning
confidence: 99%
See 3 more Smart Citations